BLOOD COMPATIBILITY OF SPUU-PEO-HEPARIN GRAFT-COPOLYMERS - PARK, KD; KIM, WG; JACOBS, H; OKANO, T; KIM, SW (JOHN WILEY & SONS INC, 1992)
Biological responses to heparinized segmented polyurethaneurea (SPUU-PEO-Heparin) were evaluated in vitro and ex vivo. In vitro assays involved plasma protein adsorption, platelet adhesion, and release reaction studies. In addition, an ex vivo rabbit arterio-artery (A-A) shunt experiment was also performed to measure occlusion times of the heparinized surfaces. All SPUU-PEO-Heparin surfaces demonstrated less protein adsorption than Biomer(R) and protein adsorption patterns similar to SPUU-PEO surfaces. Platelet adhesion and release studies demonstrated that both SPUU-PEO-Heparin and SPUU-PEO surfaces adsorbed less platelets and inhibited platelet release, as compared to Biomer (R). These findings correlated with reduction in protein adsorption observed for the modified surfaces. In low flow rate ex-vivo A-A shunt experiments, all heparinized surfaces prolonged occlusion time longer than controls. However, SPUU-PEO surfaces did not prolong occlusion time when compared to Biomer(R), although these surfaces suppressed protein adsorption and platelet interaction in vitro. The improved blood compatibility of SPUU-PEO-Heparin surfaces attest to the usefulness of this approach in improving the blood compatibility of blood contacting surfaces.
Keywords: BIOLOGICAL INTERACTIONS; IMMOBILIZED HEPARIN; FIBRINOGEN; PLATELET; SURFACES; PLASMA; ADSORPTION; PROTEINS; BINDING; RELEASE